ByzRev 07.2025.065: Eirene-Sophia Kiapidou, Byzantine Historiographical Prefaces (4th–15th Centuries):: A Study on the Praxis and Culture of Writing History in Byzantium (Byzantioς: Studies in Byzantine History and Civilization 23). Turnhout: Brepols 2025. - Polemis, Ioannis (The Byzantine Review, 2025)
Eirene-Sophia Kiapidou, Byzantine Historiographical Prefaces (4th–15th Centuries): A Study on the Praxis and Culture of Writing History in Byzantium (Byzantioς: Studies in Byzantine History and Civilization 23). Turnhout: Brepols 2025. 268 pp. – ISBN 978-2-503-61251-5